Studi Pengetahuan Mahasiswa Tentang Dampak Makanan Cepat Saji di Universitas Almarisah Madani - Fitri Adriani; Lilis Suryani; Musfira Dahlan; Ningsi Angraeni; Miranty S (Jurnal Sains dan Kesehatan, 2024)
Fast food is a top choice because it is convenient, time-saving, and can be enjoyed anytime and anywhere. In addition, it is served in a hygienic environment and is considered a prestigious and modern food, especially among young people. In Indonesia, fast food consumption is increasing, based on research from the Directorate of Public Nutrition, Ministry of Health of the Republic of Indonesia, it was recorded that in 2000, out of a total population of 210 million, around 76.7 million were overweight and more than 9.8 million were obese. This study aims to determine the level of understanding of students about the impact of fast food consumption in the DIII Midwifery Study Programme at Almarisah Madani University. The method used in this research is qualitative research with a total sample of 48 people selected using the total sampling technique. The results showed that of the 48 respondents, 43 students (89.58%) had a good level of understanding, 4 students (8.33%) had sufficient understanding, and 1 student (2.09%) had less understanding. Thus, the majority of students have good knowledge about the impact of fast food consumption.